Socioeconomic Determinants of Reversible Contraceptive Choices: Insights from A Tertiary Care Experience in India - Baskaran, Ramya; Shanthi E, Shanthi E (Journal of Neonatal Surgery, 2025)
Background and Objectives: Reversible contraceptive methods offer significant flexibility in family planning, yet their use remains relatively low in India, with a strong preference for permanent methods like sterilization. Socioeconomic factors, including education, income, and occupation, along with the availability of counselling, influence contraceptive choices. This study aims to evaluate the awareness, usage patterns, and future intentions regarding reversible contraception among women attending a tertiary care centre, and to explore the impact of these socioeconomic determinants on contraceptive decision-making. Materials and Methods: A cross-sectional study was conducted at Saveetha Medical College and Hospital, Chennai, over six months, involving 150 women aged 15–49 years. Participants were selected by consecutive sampling. Data were collected using a pre-tested, semi-structured questionnaire covering socio-demographics, contraceptive awareness, usage patterns, and influencing factors. Data were analyzed using SPSS version 25. Results: Among the 150 participants, 47.3% were primigravida and 52.7% multigravida, with 60.7% having previous LSCS. Awareness of condoms was universal (100%), while 48.7% and 51.3% were aware of DMPA injections and IUCDs respectively. Half of the women (50%) had not adopted any contraceptive method postpartum. Among users, DMPA injections (15.3%) were the most chosen method, followed by OCPs (14%) and Copper T (13.3%). Counselling significantly influenced future contraceptive intentions (p=0.021). In the three-month follow-up, among 34 participants, 79.4% reported satisfaction with their chosen method. Conclusion: Although contraceptive awareness was high, the uptake of reversible methods was limited. Socioeconomic determinants and effective counselling played a pivotal role in shaping contraceptive choices. Strengthening targeted counselling efforts is essential to bridge the gap between awareness and adoption of reversible contraception.